Correlation of Social Media Addiction to Academic Achievement in E-Learning - Sefriani, Rini; Yunus, Yuliawati; Ambiyar; Syah, Nurhasan; Fadhilah (The Indonesian Journal of Computer Science, 2023)
This study examines the relationship between students' social media addiction and student academic achievement in online lectures that use e-learning platforms. The number of study participants was 79 psychology students, who were selected using purposive sampling. The findings show that there is a positive but not significant relationship between social media addiction and academic achievement. This condition indicates that student academic achievement will increase if students reduce their addiction to using social media. Online lectures provide space for students to access social media, so direction and guidance from lecturers is needed for students not to use social media during online lectures